PENGARUH INTELLECTUAL CAPITAL TERHADAP PRODUKTIVITAS, PROFITABILITAS, NILAI PASAR PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Wany, Eva (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2010)
Based on this statement, the research to testing and analysis the influence of intellectual capital to productivity, profitability, market value, to testing and analysis the influence of intellectual capital to market value with productivity as intervening variable, to testing and analysis the influence of intellectual capital to market value with profitability as intervening variable of manufacture company listed in Indonesian Stock Exchange. Data are drawn from a sample of 48 firms from listed in Indonesian Stock Exchange using method purposive sampling. Approach of this research represent research by using multiple regression analysis. Type of data which use of this study is data documenter, the form of financial statement period of perception which Indonesian Capital Market Directory, JSX Monthly report period perception of year 2005-2007, and database Indonesian Stock Exchange